2023
DOI: 10.26668/businessreview/2023.v8i10.3547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forensic Accounting Techniques and Corporate Governance on Financial Performance of Listed Deposit Money Banks in Nigeria

Samuel Ajibade Dada,
Olusola Esther Igbekoy,
Muyiwa Emmanuel Dagunduro

Abstract: Purpose: This study aimed to investigate the effect of forensic accounting and corporate governance on the financial performance of listed deposit money banks in Nigeria.   Theoretical framework: This study drew upon Agency Theory, to provide a theoretical foundation for examining the governance of a company and the conflicts of interest that arise among its shareholders, managers, and major debt providers. This was introduced to support the concepts of forensic accounting and corporate governance.   Design/ M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…This involves evaluating the company's corporate social responsibility (CSR) initiatives, sustainability practices, ethical standards, and contributions to community development and environmental conservation. Firm performance serves as a comprehensive measure of a company's overall health, competitiveness, and ability to create long-term value for stakeholders, including shareholders, employees, customers, and society at large [22]. It is a multifaceted concept that encompasses financial, operational, strategic, and societal dimensions, providing stakeholders with insights into the company's overall success and sustainability [23].…”
Section: Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…This involves evaluating the company's corporate social responsibility (CSR) initiatives, sustainability practices, ethical standards, and contributions to community development and environmental conservation. Firm performance serves as a comprehensive measure of a company's overall health, competitiveness, and ability to create long-term value for stakeholders, including shareholders, employees, customers, and society at large [22]. It is a multifaceted concept that encompasses financial, operational, strategic, and societal dimensions, providing stakeholders with insights into the company's overall success and sustainability [23].…”
Section: Firm Performancementioning
confidence: 99%
“…A higher net profit margin indicates that the company is more effective at controlling costs and converting revenue into profits, while a lower net profit margin may suggest inefficiencies or higher expenses relative to revenue.Net profit margin is a key financial ratio used by investors, analysts, and stakeholders to evaluate a company's financial health, profitability, and performance over time. It is often compared with industry benchmarks and historical data to assess the company's competitive position and profitability trends [22].…”
Section: Net Profit Marginmentioning
confidence: 99%
“…Board size refers to the number of individuals who serve as members of a company's board of directors. It is a key aspect of corporate governance that determines the composition and structure of the board [1]. Board size can vary widely depending on factors such as the size and complexity of the company, industry norms, regulatory requirements, and corporate governance best practices [14].…”
Section: Board Sizementioning
confidence: 99%
“…While some research suggests that strong corporate governance practices can lead to improved firm performance by fostering transparency, accountability, and better decision-making, other studies have found mixed or inconclusive results. The link between corporate governance and firm performance remains a topic of ongoing research and debate, with the consensus being that effective governance structures can contribute positively to a company's long-term success and sustainability [1,4].…”
Section: Corporate Governance and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation